An Investigation On The Synthesis And Characterization Of Flexible 3d Graphene Foam - Huzaifah, Syamil Ahmad (Universiti Sains Malaysia, 2021)
Carbon materials, with their many different allotropes, have played important roles in our everyday lives as well as the advancement of material science and engineering. Since 2004, 2D graphene materials with their unique and interesting features have received significant attention after the discovery of 0D C60 and 1D carbon nanotube. 2D graphene is a single atomic layer of sp2 bonded carbon atoms which crystallizes in a honeycomb/hexagonal structure. It has an outstanding electrical property due to its two-dimensional shape, as well as a very high carrier mobility that is symmetrical for electrons and holes. Over the last decade, 3D structures have been produced out of graphene sheets which give rise to a new type of graphene materials called 3D graphene which had better and improved electrical conductivity, easy of functionalization, and large area. In this final year project, the synthesis of 3D graphene foam on copper foam was produced using methane (CH4) as a carbon source through chemical vapor deposition (CVD) process. The effect of some CVD parameters on the growth of 3D graphene on copper foam template such as growth temperature and growth time were manipulated. Afterwards, the sample was coated with poly(methyl methacrylate) (PMMA) to preserve the 3D graphene during transfer process. Then, the copper matrix was removed using nitric acid (HNO3). Next, the PMMA coating was removed by heating the samples in a Carbolite furnace. Afterwards, the 3D graphene samples produced were characterized by Raman spectroscopy and Thermogravimetric Analysis (TGA). Based on the ID/IG ratio, the sample produced at 1000°C, 40 minutes growth time has the fewest number of defects while the sample produced at 800°C, 40 minutes growth time has the highest number of defects. As the growth temperature increased from 800°C to 1000°C, the ID/IG ratio decreased which indicates that the graphene synthesized at 1000°C has fewer defects and better crystallinity than graphene synthesized at 800°C. Based on the ID/IG ratio approximates that all the graphene samples produced were multi-layered. Based on the I2D/IG ratio, the sample produced at 1000°C, 10 minutes is single layer graphene while the rest of the samples are few-layered graphene. The final mass percentage of 3D graphene and PMMA-coated 3D graphene sample is 18.46% and 13.84%, respectively. The remaining mass was the residue that was left behind which indicates that the 3D graphene was not completely pure and can be considered as low purity. Apart from that, a greater amount of heat energy is required to burn carbon nanotubes (CNT) compared to 3D graphene. This suggests that CNT is more heat resistant and have higher thermal stability than 3D graphene.